Synthesis and characterization of AlPO4-5RT molecular sieve at room temperature - Venkatathri, N. (Journal of the Indian Chemical Society, 2006)
Aluminophosphate molecular sieve AlPO4-5RT (AlPO4-5, prepared at room temperature) have been synthesized using hexamethyleneimine template at room temperature for the first time. Gel composition Al2O3 : P2O5 : 1.16HEM : 45H(2)O aging for 12 h at room temperature, and in 24 h, 473 K are the standard reaction conditions for synthesis of AlPO4-5. Studies on above gel composition at room temperature shows the presence of AlPO4-5 crystals. Both the aluminophosphates have been characterized by elemental analysis, XRD, SEM, FT-IR, TG/DTA, and C-13, Al-27 and P-31 MASNMR techniques. XRD analysis of AlPO4-5RT shows that the presence of low intensed pseudobochmite sample. SEM shows the morphology nanosized crystals along with platelets. TG/DTA analysis reveals the presence of maximum five stages elimination of templates. Carbon and nitrogen analysis shows that the presence of four template molecules per unitcell. C-13 MASNMR analysis shows the interaction of template with structure of the framework. Al-27 MASNMR shows the presence of small amount of octahedral co-ordination besides the rest are in tetrahedral co-ordination. P-31 MASNMR shows the presence of two environmentally different tetrahedrally co-ordinated phosphorous atoms.
Keywords: Aluminophosphate; Molecular sieve

Synthesis and characterization of high silica content silicoaluminophosphate SAPO-35 from non-aqueous medium - Venkatathri, N. (Catalysis Communications, 2006)
SAPO-35 with up to 15.6 Si atoms per unit cell have been synthesized, using hexamethyleneimine as template in ethylene glycol medium (molar ratio of silica in the reaction gets up to 2.5). Crystallinity and silicon incorporation was confirmed by XRD, XRF, TG/DTA, SEM, FT-IR and Al-27 and Si-29 MASNMR. These SAPO-35 materials with high Si concentration show higher activity for methanol to olefin reaction than samples prepared with up to 0.3 molar ratio of silica in the get. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ammonia adsorption; FT-IR; MASNMR; methanol to olefin; non-aqueous medium; SAPO-35; SEM; TG/DTA; XRD

Synthesis and characterization of TAPO-31 molecular sieves using tripropylamine template - Venkatathri, N.; Shetty, V. N. (Catalysis Communications, 2006)
TAPO-31 was synthesized hydrothermally using a novel template tri-n-propylamine for the first time. C and N analysis shows the butanol from titanium tetrabutoxide plays an important role in the synthesis. The incorporation of titanium into framework of phosphorous and both aluminiurn and phosphorous sites was suggested from elemental analysis. Isomorphous substitution of titanium (III) in AlPO framework was confirmed from ESR and (31)p MASNMR spectra. UV-Vis and XPS spectra revealed a partial oxidation of framework titanium (III) into titanium (IV) in the calcined TAPO-31 and thus the presence of redox centers in the products. The higher titanium content (Al/Ti = 10) TAPO-31 sample shows higher activity for phenol hydroxylation compared to lower titanium content (Al/Ti = 20) and Titanium impregnated AIPO(4)-31. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ESR; FT-IR; MASNMR; SEM; TAPO-31; TG/DTA; tripropylamine; UV-Vis; XPS; XRD

Synthesis, characterization and catalytic properties of vanadium aluminophosphate molecular sieves VAPO-31 and VAPSO-Amr from non-aqueous media - Venkatathri, N. (Applied Catalysis A-General, 2006)
Vanadium samples containing aluminophosphate molecular sieve (VAPO-31) and amorphous vanadium silicoaluminophosphate (VAPSO-Amr) have been synthesized using hexamethyleneimine template from non-aqueous media for the first time. XRD and SEM analyses confirm the phase purity of the synthesized samples. FT-IR analysis suggests the incorporation of V4+ in the aluminophosphate framework. ESR, UV-vis spectroscopic, and XPS techniques and cyclicvoltametric studies confirm the incorporation of vanadium and reveal its presence in tetrahedral and square pyramidal environments in the as-synthesized samples. Cyclic voltammetry reveals the presence of two redox couples in VAPO-31. This catalyst is found to be a good oxidation catalyst. Although most of the properties of VAPO-31NA and VAPSO-Amr are similar, the latter can access more vanadium and V4+ ions. Compared to aqueous media samples, it can incorporate more vanadium especially V5+, ions and has been found to be better oxidation catalyst. The physicochemical properties also change with media. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cyclic voltammetry; ESR; FT-IR; MAS NMR; non-aqueous; SEM; TG/DTA; UV-Vis; VAPO-31; XPS; XRD

Synthesis of high alumina ZSM-5 molecular sieve with ethylene diamine as template - Venkatathri, N. (Journal of the Indian Chemical Society, 2006)
Attempts were made to investigate compositional constraints in the synthesis of pentasill molecular sieves, including aluminosilicate zeolites using ethylene diamine (C2DN) template, from the gel composition 1.85Na(2)O : aAl(2)O(3) : 15.2SiO(2) : 592H(2)O : 19.7C(2)DN in the temperature 177 degrees C for ten days. When a = 0.25 the product was ZSM-5 and then a = 1 the product was ZSM-35 and in between compositions the mixture of two were obtained. Reduce the time of crystallization time to 5 days give nanocrystalline material. XRD and FT-IR spectra in framework region of ZSM-5 synthesized using ethylene diamine template and without template are having similar pattern, however the intensity varies. Scanning electron microscopic picture of the both are varies. The structural stability of the zeolite ZSM-5 synthesized using no template was also found to be lower as compared with that for the ZSM-5 synthesized using ethylene diamine template. These differences. may result from the occluded excess sodium.
Keywords: ethylenediamine; Molecular sieve; zeolite

Synthesis and MASNMR characterization of VPI-5 molecular sieve - Venkatathri, N. (Asian Journal of Chemsitry, 2007)
The synthesized VPI-5 sample was characterized by XRD, SEM, FTIR, TG/DTA, Al-27, P-31 and 3Q MASNMR techniques, which shows that the sample was highly crystalline. Carbon and nitrogen analysis reveals that the sample contains no template molecules; however, TG/DTA analysis shows the presence of physisorbed template molecules. MASNMR results show the presence of two different types of aluminium and phosphorus, 3Q MASNMR shows the presence of two types of environmentally different tetrahedral aluminium, which are not observable by ordinary MASNMR along with known octahedral aluminium.
Keywords: 3Q-MASNMR; FTIR; MASNMR; SEM; synthesis; TG/DTA; VPI-5; XRD

Structural and catalytic properties of a novel vanadium containing solid core mesoporous silica shell catalysts for gas phase oxidation reaction - Venkatathri, N.; Pillai, Vijayamohanan K.; Rajini, A.; Raju, M. Nooka; Reddy, I. A. K. (Journal of Chemical Sciences, 2013)
A novel vanadium containing solid core mesoporous silica shell catalyst was synthesized with different Si/V ratios by sol-gel method under neutral conditions. The synthesized materials were characterized by various techniques and gas phase diphenyl methane oxidation reaction. The mesoporosity combined with microporosity are formed by incorporation of octadecyltrichloro silane and triethylamine in the catalyst and it was found out from E-DAX and BET-surface area analysis. The material was found to be nanocrystalline. Vanadium is present as V4 + species in as-synthesized samples and convert to V5 + on calcination. Most of the vanadium is present in tetrahedral or square pyramidal environment. Incorporation of vanadium in silica framework was confirmed by Si-29 MAS NMR analysis. Among the various vanadium containing solid core mesoporous silica shell catalysts, the Si/V = 100 ratio exhibited maximum efficiency towards diphenyl methane to benzophenone gas phase reaction. The optimum condition required for maximum conversion and selectivity was found out from the catalytic studies.
Keywords: diphenylmethane; Gas phase oxidation; vanadium containing solid core mesoporous silica shell